A comprehensive classification of monetary policy frameworks in advanced and emerging economies. (20th September 2019) - Cobham, David
Abstract: The paper presents a new classification of monetary policy frameworks that it applies to advanced and emerging economies for the period since the end of the Bretton Woods international monetary system, with a focus on the monetary authorities' objectives (domestic and external), and on pre-announced targets and actual performance. The classification (available at www.monetaryframeworks.org ) also emphasizes the underlying monetary and financial infrastructure that conditions the instruments available to the authorities and, therefore, the coherence of different frameworks. It is constructed mainly from a close reading of IMF Article IV consultation reports. The two major changes revealed by the data are the trends over time towards a heavier focus on inflation, and towards more systematic and coherent monetary arrangements.